2013
DOI: 10.5194/acpd-13-22059-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-year observations of carbonaceous and nitrogenous components and major ions in the aerosols from subtropical Okinawa Island, an outflow region of Asian dusts

Abstract: Ambient aerosol samples (TSP, n=50), collected at subtropical Okinawa Island, Japan, an outflow region of Asian dusts in the western North Pacific, were studied for organic carbon (OC), elemental carbon (EC), water-soluble organic carbon (WSOC), water-soluble total nitrogen (WSTN), water-soluble organic nitrogen (WSON) and major ions to better understand the long-range atmospheric transport and formation and transformation pathways of East Asian aerosols. Concentrations of OC, EC, WSOC, WSTN and WS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 73 publications
2
27
2
Order By: Relevance
“…The size distributions of Ca 2+ and Mg 2+ were different than those observed in previous haze pollution events in Beijing, which showed that the distribution of these species primarily peaked in the coarse mode [29]. This difference might be due to the high acidity of fine particles on HP days, which improves the solubility of calcium and magnesium [50]. Ca 2+ , Mg 2+ , Na + , Na, Cr and V also exhibited similar concentration variations and may represent dust sources, including road surface dust and dust from long-range transport.…”
Section: Size Distributions Of Chemical Speciescontrasting
confidence: 53%
“…The size distributions of Ca 2+ and Mg 2+ were different than those observed in previous haze pollution events in Beijing, which showed that the distribution of these species primarily peaked in the coarse mode [29]. This difference might be due to the high acidity of fine particles on HP days, which improves the solubility of calcium and magnesium [50]. Ca 2+ , Mg 2+ , Na + , Na, Cr and V also exhibited similar concentration variations and may represent dust sources, including road surface dust and dust from long-range transport.…”
Section: Size Distributions Of Chemical Speciescontrasting
confidence: 53%
“…Wang et al (2013) also reported high WSON/WSTN ratio of 76 % in dusty aerosol samples from a semi-arid region in central China (dust storm period). In contrast, WSON/WSTN ratio in aerosol samples from Okinawa Island, Japan, an outflow region of Asian dust, was about 14% (Kunwar and Kawamura, 2014). We found that WSON does not comprise of major fraction of WSTN in the Japanese high mountain snow samples.…”
Section: Sources and Long-range Transport Of Wsonmentioning
confidence: 67%
“…Using ECtracer method, however, Kunwar and Kawamura (2014) found lower SOC to WSOC ratios in winter-spring (0.49Á 0.78) but higher ratios in summer-fall (1.53Á1.65) on Okinawa Island. Ding et al (2012) has pointed out the significant overestimation of SOC by EC-tracer method, which could result in the higher amount of SOC with respect to WSOC throughout the sampling campaigns in this study.…”
Section: Relationship Between Lg and Carbon Speciesmentioning
confidence: 96%